(untitled) (Al-Qamar, 2022)
Among the poets of past thousand years, nearly ten have remained successful in maintaining their reputation and becoming immortal. Ferdowsi and his Shahnameh are as bright as stars in the literary sky. Ferdowsi is not only known as a great poet but also a famous, wise, thoughtful leader and teacher of Iranian Nation. Moreover, he is also recognized for portraying the immorality of an individual’s freedom, independence and honor of the nation. Universal fame and acceptance of Shahnameh has honored every Iranian. The present study aims at finding answers to how Ferdowsi cleared the Concept of Iran and Iranians in literary circle worldwide through his Shahnameh? Who translated Ferdowsi’s beliefs and convictions to bring them to the world? In this article, acceptance, significance of Shahnameh and its translations in subcontinent will be discussed in detail.